2019
DOI: 10.1136/bmjoq-2018-000415
|View full text |Cite
|
Sign up to set email alerts
|

Implementing an integrated approach to self-management support in an acute major trauma therapy team: an improvement project

Abstract: More patients now survive multiple trauma injuries, but the level of long-term unmet needs is high. Evidence shows self-management support can improve patients ’ confidence to manage these needs but traditionally this support starts post-hospital. Starting self-management support early could prepare patients and families for successful transitions from hospital. The skills and commitment of clinicians have been shown to contribute to the success or failure of self-management approaches. The aim of this project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 15 publications
(38 reference statements)
0
15
0
Order By: Relevance
“…The implementation of a multi-hospital injury surveillance program in Mozambique was driven by local data collectors that enhanced the sustainability of the project [16]. Tailoring programs to local conditions is often made di cult by individuals' resistance to change [9,29]. An educational self-management intervention in a trauma centre in the UK revealed that the roll-out of support was hindered by team members preferring to continue with established practices, which limited widespread adoption [29].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The implementation of a multi-hospital injury surveillance program in Mozambique was driven by local data collectors that enhanced the sustainability of the project [16]. Tailoring programs to local conditions is often made di cult by individuals' resistance to change [9,29]. An educational self-management intervention in a trauma centre in the UK revealed that the roll-out of support was hindered by team members preferring to continue with established practices, which limited widespread adoption [29].…”
Section: Resultsmentioning
confidence: 99%
“…Prioritising patient care during implementation was widely addressed [19,29,32,36]. A Dutch evaluation of the implementation of the Transmural Trauma Care Model found that patients' experience improved as more focus was placed on day-to-day issues patients encountered [32].…”
Section: Domain 2: Outer Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…The coordination role provided by the dedicated therapy team across the MTC through completion of the rehabilitation prescription increases the identification and assessment of individuals who would benefit from a range of therapeutic interventions from appropriately trained clinicians and professional services. Consequently, we anticipate the changes to outcomes to not only be due to changes to rehabilitation, but to actually reflect the wider cultural change in modern trauma care involving greater integration of supportive and associated services, resulting in improved multidisciplinary team working [20][21][22] . It is also possible that other factors contributed to improved outcomes but were not able to be studied, such as improved expertise, equipment changes and improvements to the identification and management of trauma prior to arrival.…”
Section: Discussionmentioning
confidence: 99%